(untitled) (International relations and international law Journal, 2016)
The Republic of Kazakhstan and member-states of the economic community has become the significant part of the foreign policy, because Kazakhstan and members of the community providing development of economy increased the level of security. In the frame of the community the national economy must be identified and complementary basic to create deep intergration system, to depend on the development of international law of EAEC. Integration in the frame of EAEC overstepped the stage of free trade zone and approaches to the development of the Customs Union. The Customs Union initially was planned only for the Republic of Kazakhstan, Belarus and the Russian Federation in 2010, but Kyrgyzstan and Tajikistan planned to join after preparatory stage.. The next stage of integration was in developing single market and a single economic area.